What factors determine household food security among smallholder farmers? Insights from Msinga, KwaZulu-Natal, South Africa. Issue 1 (2nd January 2017) - Maziya, Mbongeni; Mudhara, Maxwell; Chitja, Joyce
ABSTRACT: Food insecurity persists in rural KwaZulu-Natal, South Africa. Guidelines are required to inform the formulation of programmes dealing with this challenge. Literature identifies various factors, such as agricultural skills, as key determinants of household food security. This study examines linkages between agricultural skills and household food security in farming households of the Tugela Ferry irrigation scheme in the Msinga Local Municipality. Data was collected from a random sample of 250 farming households by means of a structured questionnaire. A Tobit regression model was employed to examine the determinants of household food security. The study found that factors like household size, marital status, education level, gender, total livestock units, household income, farming experience, credit use and competence levels in fertiliser measurement have the potential to reduce household food insecurity. The study concludes that provision of agricultural skills may improve households' food security and that interventions may improve smallholder farming productivity.